Imatinib Resistance in Chronic Myeloid Leukemia Associated with a D363G BCR::ABL1 Kinase Domain Mutation - Stephen E. Langabeer; Stuart Macleod; Úna Bhreathnach; Kamal Fadalla (Case Reports in Hematology)
Acquired resistance to tyrosine kinase inhibitors (TKIs) remains a therapeutic challenge in the treatment of chronic myeloid leukemia (CML). The most studied reason for TKI resistance is the acquisition of mutations within the BCR::ABL1 tyrosine kinase domain (KDM) and of which the majority of which occur at seven codons within this region. A case of CML is described in which presence of a rare D363G BCR::ABL1 KDM resulted in a suboptimal response to frontline imatinib. Switching to dasatinib resulted in achieving a sustained major molecular response that was maintained after a subsequent switch to bosutinib due to the side effects. Reporting of such cases is important for the future management of any CML patients with this rare mutation.